The power of extraverts: Testing positive and negative mood regulation - Hervás, Gonzalo; López-Gómez, Irene (Anales de Psicología / Annals of Psychology, 2016)
Extraversion is a personality trait which has been systematically related to positive affect and well-being. One of the mechanisms that may account for these positive outcomes is the ability to regulate the responses to positive, as well as negative, moods. Prior research has found that extraverts’ higher positive mood maintenance could explain their higher levels of positive affect. However, research exploring differences between extraverts and introverts in negative mood regulation has yielded mixed results. The aim of the current study was explore the role of different facets of mood regulation displayed by extraverts, ambiverts, and introverts. After been exposed to a sad vs. happy mood induction, participants underwent a mood regulation task. Extraverts and ambiverts exhibited higher positive mood regulation than introverts, but similar mood repair. Thus, this research highlights the importance of positive mood regulation in the psychological functioning of extraverts, and opens new conceptualizations for developing interventions for introverts to improve their positive mood regulation and, hence, overall positive affect and well-being.